2017
DOI: 10.1111/lam.12785
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of anthracene by a newly isolated bacterial strain,Bacillus thuringiensisAT.ISM.1, isolated from a fly ash deposition site

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are recognized as significant health risks and consequently listed as priority pollutants by environmental protection agencies across the globe. The aim of the present study was to degrade one of the important PAHs, anthracene, by a newly isolated Bacillus thuringiensis strain. This is the first report of anthracene degradation by B. thuringiensis. This is also the very first growth kinetic study of a bacteria in an anthracene-containing medium. Some diphenol metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…GC-MS analysis has been widely used in many previous studies to identify the byproducts and metabolic intermediates produced during different anthracene biodegradation pathways by various bacterial species [17,33,59,60]. Therefore, it was selected in the current study to detect the different metabolites produced during the anthracene biodegradation and to suggest the proposed anthracene biodegradation pathways followed by the selected strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC-MS analysis has been widely used in many previous studies to identify the byproducts and metabolic intermediates produced during different anthracene biodegradation pathways by various bacterial species [17,33,59,60]. Therefore, it was selected in the current study to detect the different metabolites produced during the anthracene biodegradation and to suggest the proposed anthracene biodegradation pathways followed by the selected strains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bacillus thuringiensis AT.ISM.1 degraded anthracene through anthraquinone, phthalic acid derivatives, benzoic acid derivatives, and pyrocatechol and benzaldehyde [17]. Also, another study showed that Polyporus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was favorable when considering the degradation (%) achieved using other microorganisms reported in the literature. Numerous fungal species, such as Mycobacterium sp., were reported to degrade PAHs [35]. The transformation of PAHs using fungal species may involve several enzymatic pathways [35].…”
Section: Removal Of Polycyclic Aromatic Hydrocarbons In Test Systemsmentioning
confidence: 99%
“…Numerous fungal species, such as Mycobacterium sp., were reported to degrade PAHs [35]. The transformation of PAHs using fungal species may involve several enzymatic pathways [35]. The degradation (%) of PAHs from media containing pyrene and phenanthrene by Mycobacterium sp.…”
Section: Removal Of Polycyclic Aromatic Hydrocarbons In Test Systemsmentioning
confidence: 99%